ANTIANGIOGENESIS AND ANTIBACTERIAL ACTIVITIES FROM AN INDONESIAN MARINE-DERIVED FUNGUS Dactylaria sp - Wilmar Maarisit; Dicki Huga Tangiono; Reinhard Pinontoan; Marstella Minelko; Joke Luis Tombuku; Tan Tjie Jan (Indonesian Journal of Pharmacy, 2013)
Marine-derived fungi have been proven to be rich sources of chemically diverse natural products with a broad range of biological activities. The aim of this study was to determine the antibacterial and antiangiogenesis activities of marine derived fungi Dactylaria sp. Cultivation of the fungus Dactylaria sp (strain TID 24041021-1) was isolated from the marine invertebrate sponge. Culture of marine fungus was macerated with acetone and partitioned with ethyl acetate. The ethyl acetate extracts with 50, 100, and 200µg/mL concentrations, were assayed for their antiangiogenic activity by using chorioallantoic membrane in vivo. At the same time, ethyl acetate extracts at levels of 5, 10, 15, and 20mg/mL were assayed to pathogenic bacteria Bacillus subtilis, Escherichia coli, and Staphylococcus aureus using well diffusion method. The result of this study showed that ethyl acetate extract at concentration 50µg/mL could inhibit angiogenesis. The best antiangiogenic activity was showed at concentration of 200µg/mL ethyl acetate extract. Antibacterial activity from ethyl acetate extract inhibited the growth of B. subtilis (2.25-5mm), E. coli (0.63-3.50mm) and S. aureus (01.75mm) bacteria. Key words: Marine sponge-derived fungi, antiangiogenesis activity, antibacterial activity